Performance aspects of an injury prevention program: a ten-week intervention in adolescent female football players - Steffen, K.; Bakka, H. M.; Myklebust, G.; Bahr, R. (Scandinavian Journal of Medicine & Science in Sports, 2008)
The injury rate in football is high, and effective injury prevention methods are needed. An exercise program, the "11," has been designed to prevent the most common injury types in football. However, the effect of such a program on performance is not known. The aim of this randomized-controlled trial was to investigate the effect of the "11" on performance after a 10-week training period. Thirty-four adolescent female football players were randomly assigned to either an intervention (n=18) or a control group (n=16). The "11" is a 15-min program consisting of ten exercises for core stability, lower extremity strength, balance and agility. Performance tests included isokinetic and isometric strength protocols for the quadriceps and hamstrings, isometric hip adduction and abduction strength, vertical jump tests, sprint running and soccer skill tests. There was no difference between the intervention and control groups in the change in performance from the pre- to post-test for any of the tests used. In conclusion, no effect was observed on a series of performance tests in a group of adolescent female football players using the "11" as a structured warm-up program.